Évaluation du comportement de quelques savons traditionnels en solution aqueuse : Détermination de la concentration micellaire critique et de la température de Krafft - TOGBE, F. C. Alexis; YETE, PELAGIE; AZANDEGBE, ENI Coffi; WOTTO, VALENTIN DIEUDONNÉ (My University, 2014)
Objective: This study aims to determine some characteristic quantities of traditional soaps prepared in Benin in aqueous solution. Methods and Results: The critical micelle concentration (CMC) and the Krafft point of traditional soaps were determined by the conductivity method. The results of this study showed that conductivity of all the studied soaps had low CMC (CMC <3 g / L) and therefore are soluble and effective at room temperature. Conclusion and Application: These traditional soaps could be classified in the range of household soaps and toilet soaps.
Keywords: Savons traditionnels; concentration critique micellaire; température de Krafft; Benin